2004
DOI: 10.1002/eat.20005
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of food cravings through concurrent visuospatial processing

Abstract: Visuospatial tasks may provide a useful technique for the treatment of food craving episodes in both nonclinical and clinical populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
48
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 38 publications
(61 reference statements)
12
48
0
Order By: Relevance
“…The present findings of effects of DVN on confidence in visual STM add to a growing body of research that shows effects of DVN on visual STM (Darling et al, 2007(Darling et al, , 2009Dean et al, 2005;Dent, 2010;McConnell & Quinn, 2003-2004 as well as visual imagery performance (Dean et al, 2008;McConnell & Quinn, 2000;Quinn & McConnell, 1996a,b, 1999Smyth & Waller, 1998) and vividness (Baddeley & Andrade, 2000). This body of research appears to re-affirm Baddeley's (1986) original idea that visual imagery and visual STM are supported by one and the same visual working memory.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The present findings of effects of DVN on confidence in visual STM add to a growing body of research that shows effects of DVN on visual STM (Darling et al, 2007(Darling et al, , 2009Dean et al, 2005;Dent, 2010;McConnell & Quinn, 2003-2004 as well as visual imagery performance (Dean et al, 2008;McConnell & Quinn, 2000;Quinn & McConnell, 1996a,b, 1999Smyth & Waller, 1998) and vividness (Baddeley & Andrade, 2000). This body of research appears to re-affirm Baddeley's (1986) original idea that visual imagery and visual STM are supported by one and the same visual working memory.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, as the effect of DVN on confidence was only assessed using a recall task, it remains to be determined whether DVN reduces confidence in visual STM 13 a recognition format would also have yielded a confidence effect. A limitation is that confidence is a subjective rather than an objective measure of performance, unlike the previously used measures of memory for precise visual detail (Darling et al, 2007(Darling et al, , 2009Dean et al, 2005;Dent, 2010;McConnell & Quinn, 2003-2004. However, judgements of imagery vividness are also subjective, and these have been shown to be consistently affected by DVN (Baddeley & Andrade, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, Harvey, Kemps and Tiggemann (2005) reported a positive correlation between participants' vividness ratings of an imagined food scenario and their craving intensity, indicating that stronger food cravings are associated with more vivid images. Finally, a number of studies have demonstrated that visual processing tasks reduce food cravings in a way that auditory tasks do not (Kemps, Tiggemann, Woods & Soekov, 2004;Kemps, Tiggemann & Hart, 2005;Kemps & Tiggemann, 2007). Together, these lines of evidence lead to the conclusion that the imaginal component of food cravings is predominantly visual rather than auditory or verbal in nature.…”
mentioning
confidence: 99%